Factores de riesgo y su relación con hipertensión arterial en adultos mayores que asisten al centro de Salud By Pass Babahoyo, noviembre 2023 - abril 2024. - Garzón Riasco, Evelyn Juleixi (2024)
The study titled "Risk Factors and Their Relationship with Arterial Hypertension in Older Adults Attending the By Pass Babahoyo Health Center, November 2023 - April 2024" has been successfully carried out. The main objective was to identify the risk factors related to arterial hypertension in older adults attending the By Pass Babahoyo Health Center. To achieve this, a mixed methodological design was employed, combining qualitative and quantitative research, with a descriptive approach to meticulously detail the study results. Over a specific period of time, a longitudinal cut was conducted to obtain precise and relevant data. Inductive research methods were applied to analyze the parts of a whole, and deductive methods were used to apply logic and deduce inferences and conclusions. The target population included all older adults who attended the By Pass Health Center in the city of Babahoyo and presented problems with arterial hypertension. The survey technique with dichotomous questions was used to gather information from the older adults, while interviews were conducted with the healthcare professionals working at the center. The instruments used included a questionnaire with open and closed-ended questions to obtain detailed data on the risk factors and their relationship with arterial hypertension. The study results showed that modifiable risk factors significantly influence arterial hypertension and the health of older adults. In conclusion, it is recommended to raise awareness among patients and those responsible for their care about the importance of reducing these risk factors to ensure an improvement in the health of older adults with arterial hypertension.